Immersive virtual environment for scale cognition and learning: Expert-based evaluation for balancing usability versus cognitive theories. (September 2022) - Wu, Linfeng; Sekelsky, Brian; Peterson, Matthew; Gampp, Tyler; Delgado, Cesar; Chen, Karen B.
While scale cognition and learning is a crosscutting concept that pervades science and can aid students in making connections across disciplines, students struggle to conceptualize and consider scales that go far beyond their everyday world experience. Virtual reality technology affords embodied learning experiences, which enable students to physically engage in learning activities in an environment with rich information. Scale Worlds is a virtual learning environment implemented in an immersive CAVE, which portrays scientific entities of a wide range of sizes. A user can scale themself up or down by powers of ten, in order to experience entities from an atom to the Sun. This paper reports on an expert-based usability evaluation of Scale Worlds, including three sets of A/B testing, by five usability experts. Outcomes of the usability evaluation will inform the refinement of Scale Worlds. The evaluation provides insights for usability evaluation and design in immersive virtual environments.